Antidepressant-like effects of aqueous leaf extract of Macaranga barteri Mull. and Arg (Euphorbiaceae) in rats - N&#;Guessan Jean-Baptiste Oussou, Kouakou Léandre Kouakou, Akassi Solange Ettien, Angoué Paul Yapo, Ehouan Etienne Ehilé (Journal of Applied Pharmaceutical Science, 2021)
Some medicinal plants have shown their effectiveness in the treatment of mental disorders including depression. This study was interested in Macaranga barteri, a plant used in traditional medicine to treat anxiety. The study aimed to evaluate the antidepressant-like effect of an aqueous extract of M. barteri (AEMb) in rats and also investigate the possible mechanism(s) of the antidepressant action of AEMb. Five groups of rats were orally administered with distilled water, doses of AEMb (125, 250, and 500 mg/kg b.w.), and clomipramine (30 mg/kg b.w.). Rats were forced to swim in a cylindrical water container and walk in an open field box; their movements were recorded using a digital camera. Metergoline (a serotonin receptor inhibitor), sulpiride (a dopamine receptor inhibitor), yohimbine (a α2 -adrenergic receptor inhibitor), and prazosin (an inhibitor of α1 -adrenergic receptors) were intraperitoneally injected to other four groups of rats prior to 125 mg/kg b.w. of AEMb oral administration in order to assess the mechanism(s) of the action of AEMb. The results showed that AEMb possessed antidepressant-like effects. Its mechanism of action involved serotonergic and α1 -adrenergic receptors but it did not interfere with α2 -adrenergic and dopaminergic receptors. The antidepressant-like effect of AEMb could, therefore, justify its use in traditional medicine.
Keywords: Antidepressant, Macaranga barteri, clomipramine, rats, receptors.